The first American cancer patient to receive dicycloplatin chemotherapy: A case report. Issue 9 (2017) - Yu, Jing Jie; Salkini, Mohamad W.; Jiao, Shunchang; Hogan, Thomas; Guo, Yi; Liang, Xiaobing; Yang, Bo; Zhang, Li; Gyure, Kymberly
No abstract available